Migration of the Muhajirs in Macedonia during the Great Eastern Crisis (1875–1881) - Pandevska, Marija (Balcanica Posnaniensia. Acta et studia, 2001)
The article is devoted to the migration of muhajirs into Macedonia during the Great Eastern Crisis. The aim of the study is to determine the causes, course, and consequences of population movements triggered by the retreat of the Ottoman Empire from the Balkans. The author employs a historical method based on the analysis of sources concerning migration and ethnic transformations in the region. The research demonstrates that Macedonia was both an area from which Christian populations fled territories affected by uprisings and a destination for Muslim refugees arriving from Bosnia, Herzegovina, Serbia, and Bulgaria. The author emphasizes that the term muhajirs encompassed diverse ethnic groups, including Turks, Albanians, Bosniaks, Pomaks, Tatars, and Circassians. These migrations led to significant demographic changes and transformations in Macedonia’s ethnic and religious structure. The conclusions indicate that the population movements associated with the Great Eastern Crisis had a lasting impact on nationality relations in the Balkans and constituted an important factor in shaping the subsequent development of Macedonia.